Ligand-Promoted Palladium(II)-Catalyzed ortho-Hydroxylation of Masked Benzyl Alcohols - Huang, Ke-Yang; Wu, Ze-Yu; Luo, Jun; Jiang, Chao (Synlett, 2025)
A PdII-catalyzed ortho-C(sp²)–H hydroxylation of benzyl alcohols using an oxime ether as a monodentate directing group was developed. An N-acetylglycine ligand, in facilitating the cleavage of a C–H bond, is crucial to the reaction. The reaction might involve the formation of hydroxyl radicals generated from Oxone, and a six-membered exo-palladacycle intermediate is proposed. Various substituents on the phenyl ring were tolerated in the reaction. A gram-scale reaction and directing-group removal were also performed, demonstrating the applicability of the reaction in syntheses of salicyl alcohols.
Keywords: C(sp2)–H hydroxylation; palladium-catalysis; benzylic alcohols; oxime ethers; phenolic compounds